Transforming Educational Quality Through Total Quality Management In The Context Of Deep Learning And The National Curriculum Framework - Eddy Fadillah Safardan (International Journal of Management, Innovation, and Education, 2024)
This study aims to analyze the transformation of educational quality through the implementation of Total Quality Management (TQM) principles in schools within the framework of Indonesia’s Deep Learning-Based National Curriculum (Kurnas). The research investigates how continuous improvement, stakeholder involvement, and data-driven decision-making—core components of TQM—can enhance teaching effectiveness, institutional performance, and student learning outcomes. Using a qualitative descriptive approach, data were collected through observation, documentation, and interviews with school leaders and teachers implementing TQM practices in Bogor City vocational schools. The findings reveal that applying TQM fosters a culture of collaboration, accountability, and innovation, aligning institutional processes with the principles of the national curriculum and deep learning pedagogy. The integration of deep learning approaches—emphasizing critical thinking, creativity, and problem-solving—complements TQM’s systematic improvement cycle, resulting in more adaptive and responsive school management. However, the study also identifies challenges related to leadership consistency, teacher readiness, and digital resource constraints. Overall, the research concludes that combining TQM and deep learning within the national curriculum framework represents a strategic pathway toward sustainable educational quality transformation, bridging managerial excellence with pedagogical innovation.